Analysis of Mobile Based Activity Reporting Systems Using Usability Testing Methods and Use Questioners: Analysis of Mobile Based Activity Reporting Systems Using Usability Testing Methods and Use Questioners - Wawan Darmawan; Sunardi Sunardi; Anton Yudhana (Institute of Computer Science (IOCS), 2020)
Reporting is a part that must be prepared, monitored and evaluated by the leader in this case the director, organizational activities often overlap with each other and reporting activities are not well documented. The purpose of this study is to analyze the usability of the Activity Reporting System application. In this study the authors used the Usability Testing and USE Questioner methods. The level of usability can determine the extent to which an application or product can be used by users to achieve their goals and how easy it is to use the application interface. Applications with a high level of usability will usually be liked by many users. Vice versa, if the usability level of an application is low it will eventually be left by the user. This study also uses a USE Questioner that includes four parameters namely usefulness, ease of use, ease of learning and satisfaction. Each parameter has several statements that will be given to the user to assess the usability level of the spkditpdpontren application. The results of this study note that the usability value before the recommendation for improvement is 47.58% with sufficient predicate and the usability value after the display improvement recommendation is 78.27% with a good predicate. The general conclusion is that the activity reporting system can make it easy for users to find information related to activities and evaluation and financial management of reporting transparency and accountability.